Sequential biphasic changes in claudin1 and claudin4 expression are correlated to colorectal cancer progression and liver metastasis - Georges, Rania; Bergmann, Frank (Journal of cellular and molecular medicine, 2012)
Terminal progression of colorectal cancer (CRC) culminates in liver metastasis. To identify genes that are involved in the metastatic phenotype, cDNA microarrays were used to analyse mRNA expression profiles of colorectal carcinoma (CC)531 rat colon adenocarcinoma cells for changes related to their homing into the liver. Briefly, CC531 cells were intraportally implanted into the liver of Wag-Rij rats and re-isolated after 3, 6, 9, 14 and 21 days. Compared to control CC531 cells, claudin1 and claudin4 were among the ≥8-fold initially down-regulated genes. The co-culture of tumour cells with isolated rat hepatocytes and Kupffer cells did not induce down-regulation of either claudin1 or 4. When the environment effective on circulating tumour cells was simulated by cell culture conditions favouring their adhesion, only claudin4 showed augmented expression. Knockdown of claudin1 and claudin4 mediated by small interfering RNA caused significantly increased migration and decreased clonogenic growth of tumour cells (P < 0.05), but had no effect on their proliferation. These experimental results were paralleled by increased claudin1 and claudin4 expression in human CRC samples in Union for International Cancer Control (UICC) stages I-III, as evaluated by real-time PCR. Increased claudin4 levels were correlated with significantly reduced overall survival (log-rank test, P= 0.018). Further, significantly (P < 0.05) reduced expression of claudin1 and claudin4 was observed in stage IV and liver metastasis by immunohistochemistry. In conclusion, sequential biphasic changes in claudin1 and claudin4 expression occur during the homing of rat CC531 CRC cells to the liver. This modulation is reflected by significant changes in claudin expression in human primary and metastatic CRC.
Published: 09 March 2011
Gesehen am 04.05.2018